Utilization of Vacuum Pump in Harvesting Process of Stingless Bee Honey for Empowerment of Honey Farmer Community. - Aby, Muhammad; Putra, Reza; Muhammad, Muhammad; Rahman, Abdul; Hafiz, Ridho; Islami, Nurul (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2024)
The process of harvesting stingless bee honey requires special tools, the use of vacuum pumps as a harvesting medium makes it easier for farmers, saves time, and maintains honey quality. The purpose of this service is to provide training to the community on how to use a honey harvesting tool with a vacuum pump with a capacity of 7 liters/minute, the assembly process and maintenance. From the results of the service that has been carried out for beekeepers in Pulo Meria Village, it is found that the honey suction tool from the Vacuum pump is very useful for farmers, easy to use, production capacity of 1 liter per hour and portable. The difference in the amount of capacity is due to the different honey harvesting process due to having different sized honey bags and different honeycomb contours. From the empowerment of the honey farming community, it was found that 89% of the farmers got better quality honey harvests and increased honey production by 57% more.